Comparative morphology of leaf epidermis in 34 species of Maianthemum (Asparagaceae, Polygonateae) and their systematic significance - Meng, Ying; Wang, Jia-Jian; Nie, Ze-Long (Phytotaxa, 2016)
To investigate the possibility of using leaf epidermal characters for species identification in developing a classification for Maianthemum, we examined leaf epidermal features from across the geographic distribution of the genus, including sampling of 34 species, one subspecies and one variety, and used light and scanning electron microscopy to make observations of these features. Our results suggest that the shape of epidermal cells, and anticlinal walls on both the abaxial and adaxial leaf surface have systematic significance for defining Maianthemum taxa and are congruent with clades inferred using molecular phylogenetics. The pattern of anticlinal walls in the genus seems to be related to the geographic distribution and environmental conditions. Other characters yielded in this study including anomocytic stomata, elliptic to narrow elliptic guard cells, wrinkled, striate or nearly smooth cuticle, smooth or sinuolate to erose inner margin of the outer stomatal rim, are not useful for taxon circumscription in the genus.